Immunohistochemistry Profile of Breast Cancer Patients that Get Anthracyclin–Based Chemotherapy in RSUD Kota Bogor - Robinson, Marthino; Atmakusumah, Tubagus Djumhana; Irawan, Cosphiadi; Shatri, Hamzah (Jurnal Penyakit Dalam Indonesia, 2019)
Introduction. Breast cancer is the most prominent cancer and causing death in women. Treatment of breast cancer requires immunohistochemistry (IHC) to determine prognostic and predictive and imaging tests to determine staging. However, currently in Indonesia only 17 hospital can conduct IHC test. RSUD Kota Bogor like other Type B Hospital have no IHC test facilities. To fullfil that test, its important to refer patient to referal hospital. Because of limitation there are patients who did not do IHC test and continued get anthracycline chemotherapy. The objective of this research is to find out immunohistochemistry profile of breast cancer patients who received anthracycline-based chemotherapy in RSUD Kota Bogor. Methods. A descriptive retrospective study by collecting the breast cancer patients medical records was done since January 2014 to December 2017 in RSUD Kota Bogor. Results. Total of 174 subjects were include in this study which consist of 84 subjects (48%) with IHC test and 90 subjects (52%) without IHC test. The immunohistochemistry profile of breast cancer patients who received anthracycline-based chemotherapy since January 2014 to December 2017 in RSUD Kota Bogor were luminal type (64%), HER2-enriched (18%), and TNBC (18%). Conclusion. Luminal type is the most molecular subtypes in breast cancer patients who received anthracycline-based chemotherapy in RSUD Kota Bogor. However, because of limitation, since January 2014 to December 2017 only 48% of breast cancer patient that get anthracyclin chemotherapy who got IHC test in RSUD Kota Bogor.